EFFORTS TO IMPROVE STUDENTS' COLLABORATION AND COMMUNICATION SKILLS ON DAT PRESENTATION MATERIALS - Mega Juliana Soleh (Universitas Muhammadiyah Semarang, 2021)
Improving the quality of education, teaching and learning must be better. In the process of teaching there are several components that support them, such as, materials, teachers, students, methods, media and evaluations. These components are essential as teaching tools and thus makes it the teaching process and learning results. Currently, because of the pendemic, learning process moved it into Virtual-Learning. That makes the collaboration and communication of the between students and teachers lack understanding. Then learning process using zoom as media-learning with an additional feature, the breakout rooms aims through collaborative students can present accurate and informative data. This method used is the group discussions through small groups. Using this method, the students are more likely to collaborate and communicate because the features of breakouts rooms can create small groups so that students can interact with their groups undisturbed with students from other groups. It makes the students are enthusiastic and keenness about following the material because learning is quite differently than previously that is make students more focused on learning. Analysis indicates the number of words presented by the teacher by 2615 words while the student 4115 words, thus concluding that the student is the center of learning. With these results it can conclude that virtual learning through breakouts rooms is particularly effective as well. Keywords- Breakout rooms, Virtual learning, data concluding.